Determinants that influence customer of Bank Rakyat in selecting Islamic banking / Muhammad Syafiq Shahar - Shahar, Muhammad Syafiq (Faculty of Business and Management, 2011)
This study of “ Determinants that influence customer of Bank Rakyat in selecting Islamic Banking will concentrate the relationship between determinants that influence customer in selecting Islamic Banking with selected variables which is quality of services, religion and knowledge. From this also, it will indicate whether exist any significant relationship between the dependent variables and the independent variables. The first chapter in this study consist introduction, problem statement, purpose of the study, limitation of the study, scope of the study and significant of the study. The second chapter discuss about the literature review of the study. This chapter will concentrate on previous authors’ opinion about the study. There are authors from several books and journals were selected in order to get clear view of this study. The third part of this study is about the research methodology that had been used in obtaining the result for this research. It includes briefly explanation about the sampling design, data collection method and data analysis. The next part is finding of this study which explain the actual relationship between the dependent variable and independent variables from the processed result. The last chapter actually will discuss the conclusion and the recommendation of this study. The recommendations were based from the findings for the sake of educational purposes.